Cordycepin Ameliorates Synaptic Dysfunction and Dendrite Morphology Damage of Hippocampal CA1 via A1R in Cerebral Ischemia - Chen, Zhao-Hui; Han, Yuan-Yuan; Shang, Ying-Jie; Zhuang, Si-Yi; Huang, Jun-Ni; Wu, Bao-Yan; Li, Chu-Hua (Frontiers in Cellular Neuroscience, 2021)
Cerebral ischemia always leads to learning and memory impairments. Cordycepin has been proved to improve cognition, but the potential mechanisms are unclear so far. Plasticity of synaptic structure and synaptic function is considered one of the neural mechanisms of learning and memory. Therefore, we investigated the effects of cordycepin on dendritic morphology and synaptic transmission in cerebral ischemia and explored the relevant molecular mechanisms. The effects of cordycepin on protection against ischemia were studied by using global cerebral ischemia (GCI) and oxygen-glucose deprivation (OGD) models. Behavioral long-term potentiation (LTP) and synaptic transmission were investigated with electrophysiological recordings. Dendritic morphology and histological assessment were assessed by Golgi staining and HE staining, respectively. Adenosine A1 receptors (A1R), adenosine A2A receptors (A2AR), and adenosine content were evaluated with western blotting and HPLC, respectively. Results showed that cordycepin alleviated the GCI-induced damages of dendritic morphology and behavioral LTP in the hippocampal CA1 area, improved the learning and memory abilities, and up-regulated the level of A1R but not A2AR. In the in vitro experiments, cordycepin pre-perfusion could reduce the hippocampal slices injury and synaptic transmission impairment induced by OGD, accompanied by increased adenosine content. Furthermore, the protection of cordycepin on synaptic transmission against OGD was eliminated by using the antagonist of A1R instead of A2AR. These findings revealed that cordycepin alleviated synaptic dysfunction and dendritic injury in ischemic models by modulating A1R, suggesting that cordycepin could be used as a potential drug for treating cognitive impairment induced by cerebral ischemia.